Hysteresis modeling and position control of tendon-sheath mechanism in flexible endoscopic systems - Do, T. N. (2014)
Tendon-sheath mechanism has “revolutionized” the use of flexible endoscopic systems, by its many advantages of high maneuverability, lightweight, low cost, and simple design. However, nonlinear phenomena such as friction and backlash hysteresis present major challenges for motion control of the tool tips. This paper introduces a new mathematical model and a control scheme for the tendon-sheath mechanism for use in endoscopic systems. The asymmetric backlash hysteresis model that characterizes the transmission phenomena of the tendon-sheath mechanism in the loading and unloading phases is presented and discussed. An efficient parameter identification method is used to estimate the model parameters. Comparisons between the proposed model and experimental data validate the adoption of this new approach. A feedforward compensation method based on the asymmetric backlash hysteresis model is proposed and explored. The proposed model and control scheme are validated by experimental studies using a suitable experimental setup. The results show that the proposed model and the control scheme can improve the accuracy of tendon-sheath mechanism without using any output feedback and can be easily implemented in surgical robots using tendon-sheath mechanism as the main mode of transmission.